2009
DOI: 10.1111/j.1471-0307.2009.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Cheddar cheeses at different stages of ripening

Abstract: The aim of the study was to evaluate the changes in the antioxidant properties of Cheddar cheese at different stages of ripening using different assays: 2, 2¢-azinobis (3 ethyl benzothiazoline)-6-sulphonic acid, 2, 2-diphenyl 1, picryl hydrazyl and superoxide radical scavenging activity. Cheddar cheese was prepared with Lactobacillus casei ssp. casei 300 and Lactobacillus paracasei ssp. paracasei 22 and without adjunct cultures. The antioxidant activity of water-soluble extracts of Cheddar cheese was dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
124
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 32 publications
29
124
2
1
Order By: Relevance
“…The increases of biological activity during ripening of Cotija cheese are in agreement with other authors (Gupta et al, 2009;Pritchard et al, 2010;Ryhänen et al, 2001). Gupta et al (2009) reported that antioxidant activity and Pritchard et al (2010) reported that antioxidant and ACEI activities in the water soluble extract of cheddar cheeses depended of the stage of ripening.…”
Section: In-vitro Determination Of Ace Inhibitory Activitysupporting
confidence: 91%
“…The increases of biological activity during ripening of Cotija cheese are in agreement with other authors (Gupta et al, 2009;Pritchard et al, 2010;Ryhänen et al, 2001). Gupta et al (2009) reported that antioxidant activity and Pritchard et al (2010) reported that antioxidant and ACEI activities in the water soluble extract of cheddar cheeses depended of the stage of ripening.…”
Section: In-vitro Determination Of Ace Inhibitory Activitysupporting
confidence: 91%
“…Then, the average initial AO-WSN increased more intensively, by 37.14 % (40 days ripened cheese) and 66.58 % (50 days ripened cheese). The observed trend was consistant with the change of antioxidant properties of AO-WSN of Cheddar cheese reported by Gupta et al (2009). By comparing the results of TCA-SN and PTA-SN contents (Table 1) and the SDS-profiles of water soluble fraction it could be noticed that significant increase of AO-WSN started with more intensive secondary proteolysis.…”
Section: Total Antioxidant Capacity Of Cheese Protein Fractionssupporting
confidence: 71%
“…However, cheese ripening and proteolysis as the most complex process that occurs during ripening was identified as the major stage of their formation (Korhonen and Pihlanto, 2003). Antioxidant peptides are mostly derived from caseins due to the action of peptidases released from both, starter and non-starter lactic acid bacteria (Rival et Gupta et al, 2009). However, proteolysis of white brined cheeses prepared from overheated milk has not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the number of ripening days, a series of large and intermediate sized peptides derived from caseins began to occur due to plasmin, other proteolytic enzymes, microbial enzymes, and residual coagulant activity in the cheese. Afterward, these constituents converted to shorter peptides and amino acids by secondary microflora (Gupta et al, 2009). …”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Gupta et al (2009) examined that DPPH inhibition (%) of WSEs isolated from Cheddar cheese increased until 4 months as well. Abadía-García et al (2013) determined an increase of same (P < 0.01), with the goat milk Tulum cheese having a higher pH value around 5.87.…”
Section: Antioxidative Activitymentioning
confidence: 99%